A novel GLP-1 and FGF21 dual agonist has therapeutic potential for diabetes and non-alcoholic steatohepatitis - Pan, Qi (EBioMedicine, 2021)
BACKGROUND: Fibroblast growth factor 21 (FGF21) has become a promising therapeutic target for metabolic diseases such as type 2 diabetes (T2D), obesity and non-alcoholic steatohepatitis. However, the clinical application of natural FGF21 molecule is limited because of its instability in vitro and short half-life in vivo. To improve FGF21’s therapeutic property, we screened high receptor binding FGF21 analogs and made FGF21-Fc-GLP-1 dual-targeted constructs to investigate their activity in a number of experiments . METHODS: Utilizing phage display high-throughput screening we identified mutations that could improve β-Klotho binding property of FGF21. IgG4 Fc was fused to FGF21 variants to extend the in vivo half-life. We further explored the potential synergistic actions of FGF21 with the incretin glucagon-like peptide-1 (GLP-1) by generating GLP-1-Fc-FGF21 dual agonists. FINDINGS: Two Fc-FGF21 variants showed enhanced β-Klotho binding affinity in vitro as well as improved glucose lowering effect in vivo. One of the dual agonists, GLP-1-Fc-FGF21 D1, provided potent and sustained glucose lowering effect in diabetic mice models. It also demonstrated superior weight loss effect to GLP-1 or FGF21 alone. Moreover, GLP-1-Fc-FGF21 D1 exhibited strong anti-NASH effect in the high-fat diet-induced ob/ob model as it improved liver function, serum and hepatic lipid profile and reduced NAFLD activity score with an efficacy superior to either FGF21 or GLP-1 analogs alone. INTERPRETATION: This novel GLP-1/FGF21 dual agonist is worth clinical development for the treatment of T2D, obesity and NASH. FUNDING: HEC Pharm R&D Co., Ltd, National natural science fund of China.